2020
DOI: 10.3390/foods9121758
|View full text |Cite
|
Sign up to set email alerts
|

A Highly Sensitive “on-off” Time-Resolved Phosphorescence Sensor Based on Aptamer Functionalized Magnetite Nanoparticles for Cadmium Detection in Food Samples

Abstract: Cadmium contamination is a severe threat to food safety. Therefore, the development of sensitive and selective cadmium detection strategies is urgently required. The elimination of background autofluorescence generated from the food matrix is critical to the optical assay for cadmium detection. Herein, a time-resolved phosphorescence sensor based on an “on-off” strategy was developed for cadmium determination in food samples. The phosphorescence nanoparticles were used as a luminous material to minimize the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Aptamers have received more and more attention in the construction of biosensors in the past few years. Recently, various strategies based on aptamers for metal ion detection have been developed, including Hg 2+ [16,17], Pb 2+ [18], Cd 2+ [19] and so on. Studies had shown that thymine-thymine (T-T) mismatched duplexes in DNA can selectively bind closely to Hg 2+ to form thymine-Hg 2+ -thymine (T-Hg 2+ -T)-mediated DNA duplexes [12].…”
Section: Discussionmentioning
confidence: 99%
“…Aptamers have received more and more attention in the construction of biosensors in the past few years. Recently, various strategies based on aptamers for metal ion detection have been developed, including Hg 2+ [16,17], Pb 2+ [18], Cd 2+ [19] and so on. Studies had shown that thymine-thymine (T-T) mismatched duplexes in DNA can selectively bind closely to Hg 2+ to form thymine-Hg 2+ -thymine (T-Hg 2+ -T)-mediated DNA duplexes [12].…”
Section: Discussionmentioning
confidence: 99%
“…Rapid industrialization in recent years has led to increases in the use of Cd 2+ . Cadmium-containing pollutants in the aquatic environment are becoming increasingly common, exacerbating Cd 2+ contamination of aquatic products. To regulate the market and ensure the safety of food for humans, the World Health Organization set a standard of limited detection amount of Cd 2+ in drinking water as 0.003 mg L –1 and the Chinese government has established a maximum residue limit for Cd 2+ in food (0.0001 mg L –1 for aquatic products). , However, Cd 2+ overload in aquatic products is still common. Food has been reported to be one of the major sources of Cd 2+ exposure. Cd 2+ were detected in seaweeds, crustaceans, shellfish, and cephalopods .…”
Section: Introductionmentioning
confidence: 99%
“…3−5 To regulate the market and ensure the safety of food for humans, the World Health Organization set a standard of limited detection amount of Cd 2+ in drinking water as 0.003 mg L −1 and the Chinese government has established a maximum residue limit for Cd 2+ in food (0.0001 mg L −1 for aquatic products). 6,7 However, Cd 2+ overload in aquatic products is still common. 8−10 Food has been reported to be one of the major sources of Cd 2+ exposure.…”
Section: Introductionmentioning
confidence: 99%